THE USE OF INDONESIAN ENGLISH CODE MIXING ON CINTA LAURA’S GRADUATION INTERVIEW - Zulfikar Eko Saputro; Trisnendri Syahrizal (PROJECT (Professional Journal of English Education), 2022)
Code-mixing is a study that learns about the understanding of mixing two codes or more languages that speakers or writers situation without changing the meaning of the sentence. The study purposes to find out code-mixing was used and to find out how many codes were used in the Interview. This research method applies descriptive qualitative. The data analysis of this research is Indonesian English code- mixing on Cinta Laura’s Graduation Interview. These data are taken from a spoken interview that was written in scripts. The result of this research data are analyzed using the linguistic form in code-mixing based on Suwito’s theory, it reveals that the linguistic forms which mostly used are: “Word” (7,32%), “Phrase” (2,75%), “Clause” (1,22%), and “Word Repetition” (0,31%). Keywords:  Code-mixing, Sociolinguistic, Linguistic Form